FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI BATIK PADA INDUSTRI BATIK JAMBI DI KOTA JAMBI - Yuafni, Yuafni; Rahmiati, Rahmiati; Adriani, Adriani (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2012)
People interest to wear batik Jambi, but will make problems if batik Jambi production can supply market demand. It is affected by capital, human resources, tools and material. so, this research aimed to describe the number of capital, human resources, tools and materials that affect batik Jambi production. The kind of this research is product moment correlation with the population is all batik Jambi producer who are listed in Industry and Trading Department which are 50 industries. The samples are 50 industries taken by total sample, means that all population are samples. Data collecting did using questionnaire. The questionnaire tested by validation and reliability test, with the result of cornbach’s alpha are in high classification to highest. Data get and analyzed using computerized statisticSPSS program 12.0 version on α = 0,05. The result of that is 1) the affect of capital to batik production is 39,8%, 2) the affect of human resources to batik production is 25,6%, 3) the affect of tools and material to batik production is 50,7% and 4) the affect of all capital, human resources, tools and material to batik production is 69,1%.